2023
DOI: 10.1186/s13020-023-00726-8
|View full text |Cite
|
Sign up to set email alerts
|

The alkaloids of Corydalis hendersonii Hemsl. contribute to the cardioprotective effect against ischemic injury in mice by attenuating cardiomyocyte apoptosis via p38 MAPK signaling pathway

Abstract: Background There is a characteristic Tibetan folk medicine in China named Corydalis hendersonii Hemsl. (CH) has been used for treatment of cardiovascular related diseases, called “plethora” in Tibetan medicine. Previous studies demonstrated that ethanol extract of CH showed anti-acute myocardial infarction (AMI) effect through inhibiting fibrosis and inflammation. Rich alkaloids fraction (RAF) is isolated from CH, but whether RAF possessing an equivalent effect with the CH ethanol extract and b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Indeed, VK2 administration has been reported to exert anti-apoptotic and anti-inflammatory effects [18,42]. Furthermore, P38 MAPK pathway has been evidenced to mediate apoptosis [43]. Studies have shown that phosphorylated P38 MAPK can activate caspase-3 and promote apoptosis by downregulating Bcl-2 [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, VK2 administration has been reported to exert anti-apoptotic and anti-inflammatory effects [18,42]. Furthermore, P38 MAPK pathway has been evidenced to mediate apoptosis [43]. Studies have shown that phosphorylated P38 MAPK can activate caspase-3 and promote apoptosis by downregulating Bcl-2 [44][45][46].…”
Section: Discussionmentioning
confidence: 99%